A realistic laboratory development of an isolated wind-battery system. (June 2019) - Gan, Leong Kit; Echenique Subiabre, Estanislao Juan Pablo
Abstract: This paper details the methodology and development of an isolated wind-battery system in the lab. The full-scaled prototype was built using commercial components along with the assistance of a hardware-in-the-loop system. The integration and characterisation of a wind energy conversion system in an off-grid power system are also elaborated. Droop-based inverters interfacing batteries were used to form the isolated grid whilst a fixed speed wind turbine was employed as the main source of power generation. The former is known to be autonomous and function without communication system whilst the latter employs a squirrel cage induction generator which is robust, simple to operate and requires minimal maintenance. They were selected with the aim to reduce the technical problems which may be faced by the communities where technical assistance is scarce. We have shown that the proposed methodology presents a more controlled environment for system testing and integration whilst reproducibility of measurements can be achievable in parallel. The performance and electrical dynamics of the isolated wind-battery system are analysed with simulations and experiments. Finally, we present the capability of the test-rig in emulating the non-ideal tower shadow effect of a wind energy system. Highlights: A comprehensive isolated wind-battery model is built with its performance being tested with realistic turbulent wind model. A detail explanation of experimental setup is given along with the hardware-in the-loop system. An interfacing method is given to incorporate a practical wind turbine controller in the laboratory environment. A good correlation in terms of operation transients is shown between the simulation and experimental results. The capability of emulating wind turbine's non-ideal aerodynamic effect is demonstrated through the proposed setup.